1984
DOI: 10.1073/pnas.81.7.2232
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic and immunosuppressive activity of 2-chloro-2'-deoxyadenosine.

Abstract: The adenosine deaminase-resistant purine deoxynucleoside 2-chloro-2'-deoxyadenosine (CdA) is markedly toxic in vitro to nondividing and proliferating normal human lymphocytes and to many leukemia cell specimens. The CdA is also effective against mouse L1210 leukemia in vivo. The present investigations have examined the pharmacology, chemotherapeutic activity, and toxicity of CdA in nine patients with advanced hematologic malignancies refractory to conventional therapy. When administered by continuous intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(58 citation statements)
references
References 18 publications
2
54
0
2
Order By: Relevance
“…All IC50s were calculated from 5 or 10 point dose response curves, using the median effect method of Chou and Talaly (1987 (Nagourney et al, 1989) indicated significant cytotoxicity in a variety of human hematologic neoplasms. This was consistent with the clinical activity originally described in Phase I by Carson et al (1984) and confirmed in Phase II trials (Piro et al, 1988;Piro et al, 1990;Santana et al, 1991;Santana et al, 1992;Kay et al, 1992). Despite 2-CDA's activity in several lymphatic neoplasms, initial in vitro studies revealed little or no activity in the B cell neoplasm multiple myeloma (Nagourney et al, 1989).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…All IC50s were calculated from 5 or 10 point dose response curves, using the median effect method of Chou and Talaly (1987 (Nagourney et al, 1989) indicated significant cytotoxicity in a variety of human hematologic neoplasms. This was consistent with the clinical activity originally described in Phase I by Carson et al (1984) and confirmed in Phase II trials (Piro et al, 1988;Piro et al, 1990;Santana et al, 1991;Santana et al, 1992;Kay et al, 1992). Despite 2-CDA's activity in several lymphatic neoplasms, initial in vitro studies revealed little or no activity in the B cell neoplasm multiple myeloma (Nagourney et al, 1989).…”
Section: Resultssupporting
confidence: 65%
“…2-Chlorodeoxyadenosine is an adenosine deaminase resistant analogue of deoxyadenosine (Carson et al, 1980) which has shown clinical activity in human hematologic neoplasms in Phase I and Phase II clinical trials (Carson et al, 1984;Piro et al, 1988;Piro et al, 1990;Santana et al, 1991). Very recently two additional clinical trials have been published confirming activity of 2-CDA in acute leukaemias (Santana et al, 1992) and low grade lymphomas (Kay et al, 1992).…”
mentioning
confidence: 99%
“…Therefore, in our opinion, histomorphologic and immunohistologic examination should be repeated in those pts at 3 and 5 months, who are not in CR by core biopsy at first evaluation after 2-CdA treatment, but fullfill all other criteria for CR. A protracted effect of this purine analog is not surprising because it exerts its action on resting cells as well, and is not Sphase specific 3 Furthermore, the immunological phenotype indicates that hairy cells represent an arrest in late differentiation of B-lymphocytes between those observed in chronic lymphocytic leukemia and myeloma. Also, they are closely related to memory B-cells.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 Patients (pts) with this relatively indolent disease eventually require treatment for life-threatening pancytopenia or symtomatic splenomegaly. The first introduction of 2-chlorodeoxyadenosine (2-CdA), an adenosine deaminase (ADA)-resistant purine analog, 3 in the treatment of HCL by Piro 4 represents a milestone in modern hematology comparable to ATRA in acute promyelocytic leukemia because 2-CdA is highly effective in B-cell lymphocytes, particularly hairy cells. Following these encouraging results, several studies have reported a long-term follow-up of 3-5 years after treatment with 2-CdA.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Initial trials with 2-CdA established a maximal tolerated dose of 0.1 mg/kg per day as a continuous intravenous infusion over 7 days 23 ; however, because of its long half-life, bolus, subcutaneous, and oral regimens have been equally effective. 7,8,12,13,[15][16][17][24][25][26][27] Reported toxicities consist primarily of myelosuppression and bacterial and opportunistic infections, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] with less frequent occurrences of autoimmune hemolytic anemia 28 and neurotoxicity.…”
Section: Conclusion 2-mentioning
confidence: 99%